HIV Care in the Swedish-Danish HIV Cohort 1995-2010, Closing the Gaps - Helleberg, Marie (Public Library of Science, 2013)
BACKGROUND: Successful treatment reduces morbidity, mortality and transmission of HIV. We evaluated trends in the treatment status of HIV infected individuals enrolled in care in Sweden and Denmark during the years 1995-2010. Our aim was to assess the proportion of HIV-infected individuals who received services along the continuum of care in Denmark in 2010, and to discuss the findings in relation to the organization of the health care system. METHODS: We analyzed CD4 counts and viral loads (VL) among all HIV patients enrolled in the cohort. For each month of the study period we estimated the proportions of patients who 1) had initiated highly active antiretroviral treatment (HAART) and had VL<500 copies/mL, 2) were not eligible for HAART, 3) had initiated HAART but had VL≥500 copies/mL, 4) were eligible for, but had not initiated HAART and 5) had initiated HAART but no VL monitoring for >13 months or 6) no HAART or monitoring of CD4 for >13 months. Patients fulfilling criteria 1 or 2 were considered successfully managed. RESULTS: The proportion of successfully managed patients continued to increase throughout the study period and reached 83% in 2010, 92% of Swedish/Danish men who have sex with men and heterosexual patients, but only 74% of immigrants and 78% of injection drug users were successfully managed due to higher rates of inadequate monitoring in the latter two groups. In 2010, 70% of all individuals diagnosed with HIV in Denmark were virally suppressed. CONCLUSION: In a public health care system with free access to specialized care, successful management of the majority of HIV patients is achievable. Interventions tailored to retain immigrants and injection drug users in care are needed to further reduce the proportion of sub-optimally treated HIV patients.